The tongue as a gateway to voice, resonance, style, and intelligibility - Nair, Angelika (Plural Publishing, Inc., 2021)
"To be in the way, or to be out of the way, that is the question. Voice users and scientists alike agree that the tongue is a crucial part in singing. Yet, there has been no literature published that solely addresses the tongue and its acoustical influence in the context of technique. The Tongue as a Gateway to Voice, Resonance, Style, and Intelligibility finally answers the question which has plagued voice users: how does the tongue affect my singing and how can I manipulate it for my purpose? This book is unique in its approach to, and concentration on, the singing and speaking of consonants. In the world of voice, consonants are often overlooked, in favor of a vowel-centric approach to vocal pedagogy. By combining voice pedagogy with vocal science, Angelika Nair breaks down the mysteries of the tongue and its effect on consonant production for a fascinating new take on the human voice"--